Aotearoa New Zealand public strongly support investment in cancer treatment and care services: findings from a national survey - Virginia Signal; Ella Iosua; Kate Gregory; Rachael Neumann; Jeannine Stairmand; Jerram Bateman; Andrew Gray; Rana Peniamina; Louise Signal; Bronwen McNoe (New Zealand Medical Journal, 2026)
aim: Cancer remains a leading cause of morbidity and mortality in Aotearoa New Zealand, with rising incidence, persistent inequities and pressure on diagnosis, treatment and workforce capacity. This study examined public views on government funding, access and delivery of cancer diagnosis, treatment and supportive care services, perceptions of health workforce support and willingness to pay additional tax for healthcare funding. methods: We analysed data from a nationally representative cross-sectional online survey of adults aged 18 years or older conducted between November and December 2025. Participants were recruited using quota sampling, with oversampling of Māori and Pacific people. Weighted analyses assessed support for eight cancer funding proposals, perceptions of health workforce support and willingness to pay additional tax. results: We received 1,635 responses, with Māori (n=385; 23.5%, unweighted) and Pacific people (n=368; 22.5%, unweighted) oversampled. All eight proposals received very high support (weighted estimates were 91.4–94.4%), strongest among those aged ≥50 years, and substantial cross-party support by voting intention. Fewer than one-third (29.4%) thought the government was doing enough to support the health workforce. Most (62.3%) were willing to pay additional tax for healthcare funding. conclusion: There is strong, cross-party support for increased investment in cancer services, alongside concern about health workforce sustainability. Furthermore, there is a willingness to pay additional tax for healthcare funding.